Necrosis and necroptosis in germ cell depletion from mammalian ovary. Issue 6 (20th October 2018) - Chaudhary, Govind R.; Yadav, Pramod K.; Yadav, Anil K.; Tiwari, Meenakshi; Gupta, Anumegha; Sharma, Alka; Sahu, Kankshi; Pandey, Ashutosh N.; Pandey, Ajai K.; Chaube, Shail K.
Abstract: The maximum number of germ cells is present during the fetal life in mammals. Follicular atresia results in rapid depletion of germ cells from the cohort of the ovary. At the time of puberty, only a few hundred (<1%) germ cells are either culminated into oocytes or further get eliminated during the reproductive life. Although apoptosis plays a major role, necrosis as well as necroptosis, might also be involved in germ cell elimination from the mammalian ovary. Both necrosis and necroptosis show similar morphological features and are characterized by an increase in cell volume, cell membrane permeabilization, and rupture that lead to cellular demise. Necroptosis is initiated by tumor necrosis factor and operated through receptor interacting protein kinase as well as mixed lineage kinase domain‐like protein. The acetylcholinesterase, cytokines, starvation, and oxidative stress play important roles in necroptosis‐mediated granulosa cell death. The granulosa cell necroptosis directly or indirectly induces susceptibility toward necroptotic or apoptotic cell death in oocytes. Indeed, prevention of necrosis and necroptosis pathways using their specific inhibitors could enhance growth/differentiation factor‐9 expression, improve survivability as well as the meiotic competency of oocytes, and prevent decline of reproductive potential in several mammalian species and early onset of menopause in women. This study updates the information and focuses on the possible involvement of necrosis and necroptosis in germ cell depletion from the mammalian ovary. Abstract : Germ cell depletion from the ovary is one of the major causes that directly impact the female reproductive health in mammals. The necrosis and necroptosis are believed to be actively involved in germ cell depletion from the cohort of the ovary. Both are induced by various factors including oxidative stress, pathological conditions, and cytokines.